A new corruption index based on individual attitudes. (16th September 2013) - Bonanomi, Andrea; Osmetti, Silvia Angela
The aim of this paper is to propose a new corruption index based on individual attitudes referring to the European citizens. The index is defined by means of the person location parameters estimated by a partial credit model (PCM). This model is particularly suitable since the synthetic value of the interest latent variable 'Corruption Perception' is first evaluated at individual level; its estimated scores are then naturally aggregated to higher levels in order to obtain a measure at Europe and nation–wide.